The genus Eleocharis (Cyperaceae) in the restinga of Pará state, Brazil - Maciel-Silva,Juliene de Fátima (2018)
Abstract This work reports eight Eleocharis species for the restinga of Pará state, Brazil: E. bahiensis, E. endounifascis, E. geniculata, E. interstincta, E. minima, E. mutata, E. sellowiana, and E. urceolata. Two species are new records for the state: E. bahiensis, and E. urceolata. An identification key, morphological descriptions, taxonomic comments, and illustrations of the species in the study area are provided.